The effect of halofuginone and pirfenidone on wound healing in experimental glaucoma filtration surgery - Kasar, K.; Demir, T.; Akin, M. M.; Kobat, S. Gungor (Masson Editeur, 2021)
Purpose. - To investigate the effects of halofuginone and pirfenidone on wound healing in experimental glaucoma filtration surgery (GFS). Study Design. - Animal experimentation. Methods. - A total of 42 male New Zealand albino rabbits were separated into 6 equal groups. A limbal-based trabeculectomy was performed on 5 groups, and Group I (control group) underwent no surgery and received no postoperative medication. For Group II (sham group), 1 drop 0.9% NaCl was instilled qid for 14 days. For Group III, 1% topical corticosteroid (prednisolone acetate) was instilled 1 drop qid for 14 days. For Group IV, 0.4 mg/mL mitomycin-C (MMC) was applied intraoperatively to the region of the scleral flap. For Group V, 0.5% pirfenidone was instilled 1 drop qid for 14 days postoperatively. For Group VI, a sponge soaked in 10 ng/mL halofuginone was applied to the surgical region for 3 mins. In addition, 1% topical corticosteroid was instilled x 1 drop qid for 14 days postoperatively for Groups IV, V and VI. After 14 days, sections prepared from the bleb regions of the enucleated eyes were evaluated histopathologically and immunohistochemically. Statistical analyses of the study were performed with Kruskal-Wallis variance analysis and the Mann-Whitney U test. Results. - With regard to fibroblasts, suppression of the number of mononuclear cells and immunohistochemical staining intensity of transforming growth factor-b (TGF-beta), fibroblast growth factor-b (FGF-beta) and platelet derived growth factor (PDGF), the corticosteroid, MMC, pirfenidone and halofuginone groups were seen to exhibit more effect than the sham group( P < 0.05). Compared to the pirfenidone and fuginone groups, inhibition of fibroblast and monocyte proliferation was determined to be lower in the MMC group (P < 0.05). The intensity of TGF-beta and FGF-beta staining was seen to be lower in these two treatment groups than in the MMC group (P < 0.05). Conclusions. - Halofuginone and pirfenidone may be used as effective alternative agents in delaying wound healing in glaucoma filtration surgery. (C) 2021 Elsevier Masson SAS. All rights reserved.
L'effet de l'halofugınone et de la pırfenıdone sur la guérıson des plaıes en chırurgıe de fıltratıon expérımentale du glaucome
Keywords: Trabeculectomy; Glaucoma; Wound healing; Pirfenidone; Halofuginone